Improving the Human Resources Management Performance of Hotel Asrilia Tangerang Banten Employees - Riyanto, Slamet; Susilowati, Susilowati; Puspa , Dede; Sumerhu , Herru; Suhartono, Suhartono (The International Journal of Education Management and Sociology, 2024)
This research aims to determine and analyze human resource management in improving employee performance, and analyze SWOT for management of improving employee performance. The research uses qualitative methods. The subject of this research was the Mita Asrilia Hotel, Tangerang Banten, referring to data collection sources from hotel managers, employees and visitors. The data collection method is through interviews, observation and documentation. Meanwhile, the analysis used in this research uses descriptive qualitative analysis. The first result of this research is that the hotel employee recruitment process is carried out directly by the hotel owner through file selection and interview tests. Placement of employees according to the positions needed. The employee training and development process is carried out by managers through direction and guidance as well as procedures for serving guests. Meanwhile, the performance assessment process is carried out through assessment measures, namely work quality, cooperation, creativity, discipline and responsibility. When providing compensation, especially in the form of salaries, it is given to employees differently according to the type of work and responsibilities they carry out. Then the second is the results of the SWOT analysis. From these results, weaknesses, strengths, threats and opportunities for improving employee performance can be identified.